SELECTIVELY DIMINISHED CORPUS CALLOSUM FIBERS IN CONGENITAL CENTRAL HYPOVENTILATION SYNDROME - Kumar, Rajesh (2011)
Congenital central hypoventilation syndrome (CCHS), a condition associated with mutations in the PHOX2B gene, is characterized by loss of breathing drive during sleep, insensitivity to CO(2) and O(2), and multiple somatomotor, autonomic, neuropsychological, and ophthalmologic deficits, including impaired intrinsic and extrinsic eye muscle control. Brain structural studies show injury in peri-callosal regions and the corpus callosum (CC), which has the potential to affect functions disturbed in the syndrome; however, the extent of CC injury in CCHS is unclear. Diffusion tensor imaging (DTI)-based fiber tractography procedures display fiber directional information and allow quantification of fiber integrity. We performed DTI in 13 CCHS children (age, 18.2±4.7 years; 8 male) and 31 control (17.4±4.9 years; 18 male) subjects using a 3.0-Tesla magnetic resonance imaging scanner; CC fibers were assessed globally and regionally with tractography procedures, and fiber counts and densities compared between groups using analysis-of-covariance (covariates; age and sex). Global CC evaluation showed reduced fiber counts and densities in CCHS over control subjects (CCHS vs controls; fiber-counts, 4490±854 vs 5232±777, p<0.001; fiber-density, 10.0±1.5 vs 10.8±0.9 fibers/mm(2), p<0.020), and regional examination revealed that these changes are localized to callosal axons projecting to prefrontal (217±47 vs 248±32, p<0.005), premotor (201±51 vs 241±47, p<0.012), parietal (179±64 vs 238±54, p<0.002), and occipital regions (363±46 vs 431±82, p<0.004). Corpus callosum fibers in CCHS are compromised in motor, cognitive, speech, and ophthalmologic regulatory areas. The mechanisms of fiber injury are unclear, but may result from hypoxia or perfusion deficits accompanying the syndrome, or from consequences of PHOX2B action.